The Pathogenesis of 3 Neurotropic Flaviviruses in a Mouse Model Depends on the Route of Neuroinvasion After Viremia - Nagata, Noriyo; Iwata-Yoshikawa, Naoko; Hayasaka, Daisuke; Sato, Yuko; Kojima, Asato; Kariwa, Hiroaki; Takashima, Ikuo; Takasaki, Tomohiko; Kurane, Ichiro; Sata, Tetsutaro; Hasegawa, Hideki (Journal of neuropathology and experimental neurology, 2015)
Neurotropic flavivirus infection of humans results in viremia subsequently; in some cases, it causes meningitis encephalomyelitis, although the pathways from viremia to central nervous system (CNS) invasion are uncertain. Here, we intravenously infected BALB/c mice with 3 neurotropic flaviviruses, then examined the clinical manifestations and histopathologic changes. The Sofjin strain of tick-borne encephalitis virus–infected mice exhibited dose-dependent survival. The animals showed distention of the small intestine caused by peripheral neuritis because of infection of the myenteric plexus. Histopathologically, the strongly neurotropic Sofjin strain invaded the CNS of viremic mice via the autonomic nerves running from the plexus. The JaTH-160 strain of Japanese encephalitis virus was isolated from the lymph nodes during the preclinical phase of viral encephalitis. Therefore, this strain might infect the CNS via a hematogenous pathway, including through lymphoid tissues. The NY99-6922 strain of the West Nile virus caused clinical signs suggestive of intestinal, lymphoid, and/or neurologic involvement; the infected mice had prolonged viremia, suggesting that NY99-6922 may mainly use the hematogenous pathway; however, there was also histopathologic evidence of involvement of the autonomic nervous system pathway. In conclusion, the three neurotropic flaviviruses showed different pathogenesis, which were dependent upon overlapping but distinct pathways to CNS invasion after viremia.